Analysis of Factors Affecting Resilience among Breast Cancer Patients - Supriati, Lilik; Sudiana, I Ketut; Poeranto, Sri; Husna, Anis Rosyiatul; Rindayati, (International Journal of Psychosocial Rehabilitation, 2020)
Patients undergoing chemotherapy must have a good resilience to be able to rise to face the problems caused by the physical and psychological side effects of chemotherapy. Resilience is influenced by many factors. The study aims to analyze the factors related to resilience among breast cancer patients, including age, time of illness duration, cycle of chemotherapy, social support and family support. This study used observational analytic method with cross-sectional approach. The population in this research comprised breast cancer patients who received 2- 6 sessions of chemotherapy at Army Hospital Level II of dr. Soepraoen Malang. The total sample in this study had 62 patients taken by using a purposive sampling technique. Data collection was conducted by using questionnaires. The data were analyzed through a univariate and linear regression test with a significance level of α ≤ 0,05. The test result showed that out of the 5 independent variables two significantly influenced patient’s resilience, namely family support and social support. Social support is the variable that has the greatest influence on the resilience of breast cancer patients. So, nurses need to pay attention to providing social support in nursing services in breast cancer patients to improve their resilience.